2015
DOI: 10.1177/1098612x15576980
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intravenous adipose-derived allogeneic mesenchymal stem cells for the treatment of feline chronic kidney disease: a randomized, placebo-controlled clinical trial in eight cats

Abstract: While administration of MSC culture expanded from cryopreserved adipose was not associated with adverse effects, significant improvement in renal function was not observed immediately after administration. Long-term follow-up is necessary to determine whether MSC administration affects disease progression in cats with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 25 publications
(69 reference statements)
1
67
0
4
Order By: Relevance
“…Cats are a particularly important translational model for a number of diseases that are similar in cats and humans, including FIV (HIV) [61], T cell-mediated oral mucosa inflammation [24], chronic renal failure [29], asthma [25], chronic enteropathy [26], and osteoarthritis. The goal of this work was to profile feline ASCs and directly compare their phenotypic, cellular, and immunomodulatory profiles with human ASCs to deepen our understanding of MSC-based therapies as we move towards mechanism-of-action studies in animals and people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cats are a particularly important translational model for a number of diseases that are similar in cats and humans, including FIV (HIV) [61], T cell-mediated oral mucosa inflammation [24], chronic renal failure [29], asthma [25], chronic enteropathy [26], and osteoarthritis. The goal of this work was to profile feline ASCs and directly compare their phenotypic, cellular, and immunomodulatory profiles with human ASCs to deepen our understanding of MSC-based therapies as we move towards mechanism-of-action studies in animals and people.…”
Section: Discussionmentioning
confidence: 99%
“…For example, feline chronic gingivostomatitis has a similar T-cell activation phenotype to the human oral inflammatory diseases oral lichen planus, apthous stomatitis, and pemphigus vulgaris [27, 28]. Cats also serve as valuable models for noninflammatory diseases, including chronic renal failure [29, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…The few published studies on MSC treatment in cats with CKD have evaluated IV or intrarenal delivery of stem cells . Although safety of MSC treatment was demonstrated repeatedly, improvement in renal function was not a consistent finding.…”
Section: Introductionmentioning
confidence: 93%
“…Likewise, in the rhesus monkey, MSC administration ameliorated AKI induced by cisplatin to some extent but did not reverse established interstitial fibrosis . Autologous AdMSCs have been the primary cell source used in feline preclinical models, but none of the studies have been able to replicate the efficacy reported in rodents . Differences between rodent and feline kidneys certainly explain some of these results, which are discouraging as feline CKD more closely resembles human pathology.…”
Section: Interpreting Reports Of Stem Cell Therapies For Kidney Diseasementioning
confidence: 99%